1982
DOI: 10.1136/bjo.66.6.398
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus and response AC/A ratios in intermittent exotropia of the divergence-excess type.

Abstract: SUMMARY Objective infrared recording devices were used to measure simultaneously and continuously both accommodation and accommodative vergence to near stimuli in 4 subjects with intermittent exotropia of the divergence-excess type (2 simulated and 2 true). In addition standard clinically determined stimulus accommodative convergence to accommodation (AC/A) ratios were measured. Results showed the mean group response AC/A ratio to be 5-9/1 (range 4 5-8 0/1) with no differences between true and simulated diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 19 publications
3
49
0
1
Order By: Relevance
“…Kushner, 3,4,8 Cooper and colleagues, 9 and Arnoldi and Reynolds 5 have suggested that adaptive fusional vergence (''tenacious proximal fusion'' or ''fusional vergence aftereffect'') plays a more significant role in reducing the size of the deviation at near than a patient's accommodative convergence. This is supported by the clinical finding that many patients with a high AC/A ratio do not develop a postoperative consecutive near esotropia.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kushner, 3,4,8 Cooper and colleagues, 9 and Arnoldi and Reynolds 5 have suggested that adaptive fusional vergence (''tenacious proximal fusion'' or ''fusional vergence aftereffect'') plays a more significant role in reducing the size of the deviation at near than a patient's accommodative convergence. This is supported by the clinical finding that many patients with a high AC/A ratio do not develop a postoperative consecutive near esotropia.…”
Section: Discussionmentioning
confidence: 98%
“…[5][6][7][8] Studies have also indicated that monocular occlusion is required prior to measurement of the AC/A ratio 4,5,9 due to adaptive fusional vergence effects, commonly referred to as ''tenacious proximal fusion'' or ''fusional vergence aftereffect,'' contaminating the measurement. 4,9 However, the AC/A ratio is influenced not only by the presence of tenacious proximal fusion but also by a patient's accommodative response to lenses during testing. The purpose of using plus or minus lenses in measuring the AC/A ratio is to, relax or induce accommodation and the related accommodative convergence, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8,20 In general, patients with intermittent exotropia, especially when the eyes are aligned, may have relatively normal binocular function. [21][22][23] When the Titmus stereo test was used to measure stereoacuity in patients with intermittent exotropia, it averaged 41 arcsec, similar to the stereoacuity level in normal populations. 13,24 Compared with this level of stereopsis, our patients with intermittent exotropia and DVD had poorer stereopsis, with an average of 147 arcsec.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is little difference in the responses for H compared with NG, DG or SG, with participants stating 3:1 to be the normal ratio most often in all four methods, closely followed by 4:1 -yet anecdotal evidence and published data 5,7,8 have demonstrated that there are significant differences in measured AC/A ratios between these methods. Commonly clinicians will anecdotally attest that H often over-estimates the AC/A ratio compared with either gradient method, and in fact Garretty 8 demonstrated a 5-6:1 ratio using H compared with 2-3:1 with NG and DG, which was statistically significant ( p < 0.01).…”
Section: Perception Of the 'Normal' Ac/a Ratiomentioning
confidence: 99%